Eco-friendly stereoselective reduction of α, β-unsaturated carbonyl compounds by Er(OTf)3/NaBH4 in 2-MeTHF. Issue 7 (18th February 2015) - Nardi, Monica; Sindona, Giovanni; Costanzo, Paola; Oliverio, Manuela; Procopio, Antonio
Abstract: An operationally simple and environmentally benign catalytic procedure has been developed to selectively reduce different α, β-unsaturated ketones. The corresponding allylic alcohols are obtained with high chemo- and diastereoselectivity using Er(OTf)3 and NaBH4 in 2-MeTHF. This protocol reduces the amount of catalyst and NaBH4 needed, compared to classical procedures and the stages of extraction/purification are carried out in aqueous solutions avoiding the use of toxic solvents. Taking into account that Er(OTf)3 can be considered even less toxic than table salt and the 'greenness' of 2-MeTHF as a solvent, the system Er(OTf)3 /2-MeTHF can be proposed as a cheap, efficient, and environmentally sustainable reduction system for the synthesis of allylic alcohols. Graphical abstract: